Sadie and Ratz - Hartnett, Sonya; James, Ann, 1952- (Somerville, Mass. : Candlewick Press, 2013)
Hannah and her hands, named Sadie and Ratz, regularly get into trouble, especially when younger brother Baby Boy is around.
Kirkus Starred
Pub Weekly
School Library Journal starred
Booklist, May 2012
Horn Book, November 2012
Kirkus Starred, January 2012
Keywords: Brothers and sisters -- Juvenile fiction; Hand -- Juvenile fiction; Human behavior -- Juvenile fiction; Imagination -- Juvenile fiction; Brothers and sisters -- Fiction; Hand -- Fiction; Human behavior -- Fiction; Imagination -- Fiction; Hand -- Fiction; Human behavior -- Fiction; Imagination -- Fiction; Siblings -- Fiction